Critical Synthesis Package: East Tennessee State University Common Ground Assessment Instrument - Angela Wetzel (Association of American Medical Colleges, 2014)
Abstract The Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the East Tennessee State University Common Ground Assessment Instrument (CGAI), and (2) a copy of the CGAI and guidelines for use developed by Forrest Lang, MD. The CGAI assesses communication skills in a common office-based medical interview using checklists and global rating scales across the categories of: Rapport, Eliciting All Agenda Items, Information Management, Active Listening for Full Understanding of Ideas, Concerns and Expectation, Addressing Feelings with Patient, Closing the Interview, and Reaching Common Ground. The CGAI is rated among one of the more comprehensive assessments of communication competence with strong psychometrics, alignment to key content areas, adequate usability, and a high generalizability coefficient using just five to eight cases. Originally developed and tested to assess learner communication competence within a standardized patient setting, the CGAI has been both adapted and applied in a formative clinical skills examination, and used as a measure of physician communication competence in a primary care setting. Guidelines for the use of the CGAI are provided by the developers, and it is suggested that the CGAI can be rated by both trained raters as well as faculty. To date, the literature only reports on studies employing trained raters; further research with faculty raters can inform necessary training and subsequent usability by a broader group of evaluators.